PENGARUH PENERAPAN RULE OF LAW, CONSENSUS ORIENTATION, DAN EQUALITY TERHADAP KESEJAHTERAAN MASYARAKAT DI MASA PANDEMI COVID-19 (STUDI KASUS PADA DESA TOTOKATON KECAMATAN PUNGGUR) - Tri Suci Rahayu; Nedi Hendri; Angga Kurniawan (Jurnal Akuntansi AKTIVA, 2021)
This study aimed to analyze the effect of rule of law (1), consensus orientation (2), and equality (3) on community welfare. This study used a quantitative approach, the population of this study was 151 respondents. The sampling technique in this study was probability sampling using simple proportional random sampling with the Slovin formula, so as to obtain a sample of 60 respondents. The data in this study used SPSS version 20 with multiple linear regression analysis testing. The results of this study indicated that the rule of law had a significant effect on people's welfare, while consensus orientation and equality did not have a significant effect on people's welfare.